Economics and Management of Franchising Networks - Windsperger, Josef; Cliquet, Gérard; Hendrikse, George; Tuunanen, Mika (Physica-Verlag HD, 2004)
Franchising networks are experiencing great success in international business organization. Few books try to explain the characteristics of these networks. Contrary to the existing literature this book tackles more theoretical problems related to governance, organization, knowledge management, contract design, incentive and regulation issues both from the economic and management view point. It delivers new theoretical and empirical results regarding plural forms, contract design, and knowledge and strategic management issues. Its purpose is to offer researchers and practitioners new theoretical and empirical insights in one of the most important economic phenomenon at the beginning of the 21st century: Franchising networks as organizational arrangement for growth and internationalization of firms
Keywords: Organization; Industrial Organization; Marketing; Planning; Industrial organization; Management; Investitionsplanung; Wirtschaftlichkeit; Franchising; Netzwerkmanagement; Wirtschaftlichkeitsrechnung; Investitionsrechnung; Netzwerk; Konferenzschrift -- 2003 -- Wien